ANALISA PENGETAHUAN SIKAP DAN PERILAKU PENGANGKUT SAMPAH TERHADAP ASPEK KESELAMATAN KESEHATAN KERJA DALAM PENGOLAHAN SAMPAH - Marzuki Samion (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2019)
The purpose of this research is to knowing correlation of knowledge, attitute and practice of garbage attendant laborers of aspects of occupational health and safety against waste processing at TPS in Pasir Pangaraian Rokan Hulu Riau. This research uses analytical method with cross sectional design. The population in this study were all Garbage attendant Laborers at TPS in Pasir Pangaraian amounted to 64 people with total sampling method. Data analysis using chi square test indicated that there is correlation between knowledge with occupational health and safety at TPS in Pasir Pengarain. Value p = 0.026 < 0,05 indicate that there is correlation between attitute with occupational health and safety at TPS in Pasir Pengarain. The value of p = 0.034 < 0.05 indicates that there is correlation between practice with occupational health and safety in TPS in Pasir Pengarain Conclusion: There is a relationship of Attitude, Knowledge and Practice with occupational health and safety at TPS in Pasir Pengarain.